2022
DOI: 10.1186/s12889-022-13911-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of globalization, energy consumption and ICT on health status in Australia: the role of financial development and education

Abstract: Background The outbreak of COVID-19 has alerted governments around the world, including Australia, to think seriously about the health issues. Life expectancy is one of such issues. Therefore, this study tries to reveal the effects of globalization, energy consumption, information and communication technology, financial development, education rate, and economic growth on life expectancy at birth in Australia. Methods Using the data period of 1990–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
2
7
0
2
Order By: Relevance
“…In another study, Adom et al (2021) showed that improving renewable energy could make adequate capacity for tolerating energy shocks and so facilitate improvements in development outcomes; for example, GDP per capita, employment, human capital, environmental health and life expectancy. There are also similar papers with identified findings, such as Rodriguez (2021), Rahman and Alam (2022a, 2022b).…”
Section: Literature Reviewsupporting
confidence: 72%
“…In another study, Adom et al (2021) showed that improving renewable energy could make adequate capacity for tolerating energy shocks and so facilitate improvements in development outcomes; for example, GDP per capita, employment, human capital, environmental health and life expectancy. There are also similar papers with identified findings, such as Rodriguez (2021), Rahman and Alam (2022a, 2022b).…”
Section: Literature Reviewsupporting
confidence: 72%
“…Second, the positive link between RNEW and LEXP is confirmed in the studies of Abbas et al (2022), Alharthi et al (2022), Rahman and Alam (2022a), Alam (2022b), andYoussef et al (2015). Youssef et al (2015) stated that clean energy use could benefit human health in different ways, such as a reduction in the rate of child mortality, the adequate storage of basic medicines, the improvement of maternal health, and provides access to ICT and applications of E-health.…”
Section: Discussionmentioning
confidence: 88%
“…In Australia, New Zealand, United States, Belgium, Netherlands, and Luxembourg (ANZUS‐BENELUX) economies, Rahman and Alam (2022a) discovered that RNEW and GDP improve LEXP. In Australia, Rahman and Alam (2022b) discovered that RNEW increases LEXP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The socioeconomic factors-health gradient has continued to be studied with more recent studies such as Benos, Karkalakos, and Zotou (2019); Ehmann, Groene, Rieger, and Siegel (2020); Pothisiri, Prasitsiriphon, and Aekplakorn (2020) and Rahman and Alam (2022) supporting the health-advantage effect of socioeconomic factors in Australia, Germany, Thailand and the US respectively as well as Karma (2023);Miladinov (2020) Raghupathi and Raghupathi (2020) and Nwude et al (2020) for panels of European, OECD and African countries respectively. However, a considerable amount of research has also suggested that socioeconomic factors do not significantly predict health outcomes despite the wide range of evidence supporting the positive impact of socioeconomic factors on health.…”
Section: Literature Reviewmentioning
confidence: 99%